The Role of CXC Chemokine Receptors 1–4 on Immune Cells in the Tumor Microenvironment - Susek, Katharina Helene; Karvouni, Maria; Alici, Evren; Lundqvist, Andreas (Frontiers in Immunology, 2018)
Chemokines govern leukocyte migration by attracting cells that express their cognate ligands. Many cancer types show altered chemokine secretion profiles, favouring the recruitment of pro-tumorigenic immune cells and preventing the accumulation of anti-tumorigenic effector cells. This can ultimately results in cancer immune evasion. The manipulation of chemokine and chemokine-receptor signalling can reshape the immunological phenotypes within the tumor microenvironment in order to increase the therapeutic efficacy of cancer immunotherapy. Here we discuss the three chemokine-chemokine receptor axes, CXCR1/2–CXCL1-3/5-8, CXCR3–CXCL9/10/11, and CXCR4-CXCL12 and their role on pro-tumorigenic immune cells and anti-tumorigenic effector cells in solid tumors. In particular, we summarize current strategies to target these axes and discuss their potential use in treatment approaches.